Ultrathin Functional Polymer Modified Graphene for Enhanced Enzymatic Electrochemical Sensing - Owen Guy (Biosensors, 2019)
Grafting thin polymer layers on graphene enables coupling target biomolecules to graphene surfaces, especially through amide and aldehyde linkages with carboxylic acid and primary amine derivatives, respectively. However, functionalizing monolayer graphene with thin polymer layers without affecting their exceptional electrical properties remains challenging. Herein, we demonstrate the controlled modification of chemical vapor deposition (CVD) grown single layer graphene with ultrathin polymer 1,5-diaminonaphthalene (DAN) layers using the electropolymerization technique. It is observed that the controlled electropolymerization of DAN monomer offers continuous polymer layers with thickness ranging between 5–25 nm. The surface characteristics of pure and polymer modified graphene was examined. As anticipated, the number of surface amine groups increases with increases in the layer thickness. The effects of polymer thickness on the electron transfer rates were studied in detail and a simple route for the estimation of surface coverage of amine groups was demonstrated using the electrochemical analysis. The implications of grafting ultrathin polymer layers on graphene towards horseradish peroxidase (HRP) enzyme immobilization and enzymatic electrochemical sensing of H2O2 were discussed elaborately.